Analisis Hukum Pemalsuan Merek pada Tiktok Shop - Kenjiroh, Benny; Hosna SH. MH. , Dr. Hj. Asmak Ul (Interdisciplinary Explorations in Research Journal, 2025)
Brand counterfeiting on e-commerce sites such as TikTok Shop is a significant legal issue. The TRIPS Agreement governs protection at a global level. The purpose of this research is to examine the legal framework and its legal consequences for actors, the original owner of the mark, and consumers. The research found law enforcement issues due to the cross-border nature of e-commerce. This research utilizes a qualitative approach and descriptive analysis. Brand owners and consumers receive better protection, while perpetrators receive civil and criminal sanctions. Recommendations include improving e-commerce, government cooperation, and consumer training.